(untitled) (Research, Society and Development, 2021)
Objective: Analyze the impacts of cervical cancer on women’s sexuality, evidencing its importance for quality of life. Methods: This is an epidemiological, descriptive and analytical study, with cross-sectional data collection. Eighty women with cervical câncer, undergoing treatment or already treated, were interviwed in the oncology clinic of Hospital de Urgência de Sergipe, through two questionnaires. The first one results in socioeconomic and demographic aspects. The second one, in Female Sexual Quotient version (QS-F). The data was analyzed using descriptive statistics using the Epi-Info version 7.0 software. The work was submitted and approved by the Research Ethics Committee considering it is a rsearch oh human beigns. Results: The average age was 46.8 years (± 13.2). Education level was 25% higher (n = 20). Regarding marital status, socioeconomic status and professional one, 36.3% (n = 29) declared themselves married, 51.2% (n = 41) from the middle class and 33.8 (n = 27) doing “home” activity. The QS-F had an overall average of 45.5 points (± 23.9), ranging from 10 to 84 points. Adopting the stratified classification, it was observed that a big number of women, 85% (n = 68), were classified as regular or inferior. There was a statistically significant difference between the strata of the QS-F and the socioeconomic level. Conclusion: The present study corroborates with the literature used in several areas, since most of the women questioned showed low and unsatisfactory sexual function according to the QS-F.